Case Report: Ethanol ablation of the Marshall vein as the first step for left atrial tachycardia ablation - Ozgeyik, Mehmet; Dural, Ibrahim Etem; Baysal, Erkan; Li, Anthony; Candemir, Basar (Frontiers in Cardiovascular Medicine, 2024)
Electroanatomic mapping guides complex atrial tachycardia ablations; however, challenges may emerge after pulmonary vein isolation. 3D mapping systems can reveal the mechanism of tachycardia and critical areas that need to be ablated. Sometimes, however, these areas may be located deep inside, to the extent that they cannot be successfully reached by endocardial ablation. In this study, we present a unique case of a patient in whom vein of Marshall (VOM) ethanol ablation, a conventional secondary intervention, promptly terminated a Marshall bundle–related atrial tachycardia without further endocardial radiofrequency application, suggesting VOM ethanol ablation as a potential primary strategy.